Improving students’ attendance in Values Education classes during Catch-Up Fridays through collaborative game-based learning - Barcos, Ivann P.; Libres, Erica V.; Angcay, Jessa L.; Bitos, Maeriel D.; Juaton, Jessel Mae P.; Juanillo, Caryl Kaye B.; Bansale, Jay C. (Indonesian Journal of Education and Pedagogy, 2025)
This study aimed to improve the attendance of 36 Grade 8 Santan students in Values Education classes during Catch-Up Fridays through Collaborative Game-Based Learning. Using a mixed-method design, the study evaluated attendance trends before and after the intervention. Quantitative data were collected from School Form 2 (SF2) to measure attendance, and a paired sample t-test revealed a significant increase in mean attendance values, from 3.47 to 4.47, with a p-value of less than 0.05, confirming the intervention's effectiveness. Qualitative data were gathered through a focus group discussion (FGD) and a thematic analysis following Braun and Clarke's (2006) framework was used to examine how students find Collaborative Game-Based Learning as an intervention to improve attendance. Students’ responses from the FGD showed that Collaborative Game-Based fosters student engagement, enhances participation, and creates a fun and dynamic learning environment.